A methodological proposal for the analysis of disused railway lines as territorial structuring elements: The case study of the Vasco-Navarro railway. (February 2020) - Eizaguirre-Iribar, Arritokieta; Grijalba, Olatz
Highlights: Disused railways have potential as non-motorised territorial structuring axes. The analysis method enables to understand disused railway as complex systems. Areas, where similar guidelines can be implemented, have been identified. Abstract: The thousands of kilometres of disused railway lines that make up a fascinating body of heritage have been the subject of studies by several authors over recent decades. Several interventions for their reuse and reconversion have been carried out. However, there is a mismatch between theoretical and practical achievements. This research claims that an analysis of the railway lines under discussion should develop a comprehensive vision in order to establish common criteria for their preservation and for future interventions. As such, the objective of this paper is to create a methodological proposal for the analysis of disused railway lines as complex systems, thus demonstrating their potential as part of situated proposals for sustainable development. Accordingly, a Comprehensive Analysis Method (CAM) is created based on three theoretical and methodological underpinnings: disused railways as heritage systems; former linear infrastructures as non-motorised axes; and a balance between transport and other land uses around former railway nodes. The conclusions make reference to the potential of disused railways as territorial structuring systems, including both the potential of the linear infrastructure and the potential of the railway nodes, in order to encompass repurposing beyond the current greenways while continuing to promote the preservation of railway heritage. Both general strategies and specific action points have been identified for the repurposing of disused railway infrastructure. The proposed methodology has been applied in the case study of the Vasco-Navarro Railway, identifying strategic points in the infrastructure and areas where specific strategies can be implemented.